The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00249-008-0362-4
|View full text |Cite
|
Sign up to set email alerts
|

Detailed state model of CaMKII activation and autophosphorylation

Abstract: By combining biochemical experiments with computer modelling of biochemical reactions we elucidated some of the currently unresolved aspects of calciumcalmodulin-dependent protein kinase II (CaMKII) activation and autophosphorylation that might be relevant for its physiological function and provided a model that incorporates in detail the mechanism of CaMKII activation and autophosphorylation at T286 that is based on experimentally determined binding constants and phosphorylation rates. To this end, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 47 publications
0
27
1
Order By: Relevance
“…75,76 CaMKII subunits undergo cis-phosphorylation; pairing of subunit's catalytic domains allows for phosphorylation in trans, but this only occurs if both subunits are activated through Ca 2C /CaM binding. 74,[77][78][79] CaMKII has been implicated in EMT in development. 80 In xenopus development, CaMKII activation is seen in EMT and migration of fin core cells.…”
Section: Molecular Regulation Of Epithelial Scattering By Calcium/calmentioning
confidence: 99%
“…75,76 CaMKII subunits undergo cis-phosphorylation; pairing of subunit's catalytic domains allows for phosphorylation in trans, but this only occurs if both subunits are activated through Ca 2C /CaM binding. 74,[77][78][79] CaMKII has been implicated in EMT in development. 80 In xenopus development, CaMKII activation is seen in EMT and migration of fin core cells.…”
Section: Molecular Regulation Of Epithelial Scattering By Calcium/calmentioning
confidence: 99%
“…Simulation studies have shown that this phenomenon could be achieved without holoenzyme formation, if the various rate constants and concentrations are tuned appropriately (see, for example, [61,62]). An important role for the oligomeric structure is probably to bring the enzyme and substrate CaMKII into close proximity so that the rates of transphosphorylation and release of inhibition are matched appropriately to the Ca 2+ spike frequency.Importantly, the duration of each Ca 2+ pulse will affect the frequency threshold – a shorter pulse duration will necessitate a higher threshold frequency for activation and vice versa.…”
Section: Holoenzyme Structurementioning
confidence: 99%
“…Following an increase in Ca 2+ , CaMKII is activated and autophosphorylated [55]. The holoenzyme kinase subunits are activated by Ca 2+ /CaM binding, resulting in phosphorylation of target substrates, and rapid intersubunit autophosphorylation of several sites [18,55].…”
Section: Structure-function Of the Multifunctional Ca2+/calmodulin-stmentioning
confidence: 99%
“…The holoenzyme kinase subunits are activated by Ca 2+ /CaM binding, resulting in phosphorylation of target substrates, and rapid intersubunit autophosphorylation of several sites [18,55]. Autophosphorylation of Thr286 (numbering according to α isoform, Thr287 for β, γ and δ) by adjacent subunits disrupts the interaction of the autoinhibitory domain with the catalytic domain, and converts the holoenzyme into a Ca 2+ /CaM independent kinase (autonomous activity) that allows CaMKII to continue to phosphorylate its substrates after cytosolic Ca 2+ levels decrease [11,55]. In addition, the affinity of CaMKII for CaM increases about 1000-fold, a phenomenon termed ‘CaM trapping’ [56].…”
Section: Structure-function Of the Multifunctional Ca2+/calmodulin-stmentioning
confidence: 99%